THE CONSTRUCTION OF INDONESIAN FAMILY LAW IN THE PERSPECTIVE OF ISLAMIC LAW: A CONCEPTUAL REVIEW AND IMPLEMENTATION: Konstruksi Hukum Keluarga Indonesia dalam Perspektif Hukum Islam: Tinjauan Konseptual dan Implementasi - Mulyadi; Muhammad Fadhlan; Kusnadi; Siarman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This article examines the construction of family law in Indonesia from an Islamic legal perspective, focusing on conceptual review and implementation within the national legal system. As the largest Muslim-majority country, Indonesia integrates Islamic legal principles into family law through regulations such as the Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), which serve as guidelines for religious courts. This study utilizes a literature review method to analyze various sources discussing Islamic legal principles in marriage, divorce, child custody, and inheritance. The findings indicate that while Islamic family law has successfully adapted within the national legal context, challenges remain, particularly concerning gender equality, child protection, and the need for flexible legal interpretation. The relevance of Islamic law in Indonesian family law requires contextual ijtihad to address contemporary issues without compromising its core values. This study underscores the importance of engaging scholars, academics, and stakeholders in reforming Islamic family law to align with social justice principles within Indonesia's multicultural society.